Origin of Ankara Castle Rampart Building Stones - Kıymet Deniz; Yusuf Kağan Kadıoğlu (Ankara Araştırmaları Dergisi, 2022)
In order to properly protect and restore cultural assets, it is important to correctly identify the natural materials used in historical buildings and determine the origin of these materials and the quarries they were taken from. This study therefore examines the rampart building stones of Ankara Castle, which is one of the most important historical buildings in the city, and determines the locations of the quarries used in its construction. In the study, samples were taken from the castle, rampart walls and the rocks in the castle's foundation. The samples were then compared mineralogically, petrographically and geochemically with other samples taken from quarries where the stones may possibly have originated from. Ankara Castle, which is located in the Altındağ district of Ankara, is comprised of an inner and an outer castle. The castle was basically built on vertically articulated andesite rock and has the same composition as the rampart stones. Brick and limestone were also used in certain parts of the rampart walls. The rampart stones are mainly composed of pink porphyroafanitic textured andesites, but also contain locally crystallized and biosparitic limestone. Andesites are seen to have a hyaloplitic porphyritic texture when examined under the microscope, and consist mainly of plagioclase, amphibole, biotite, pyroxene, +- quartz and opaque minerals. Quartz and plagioclase crystals are embayed and the plagioclase was also zoned. Kaolinization, chloritization and opacification type alterations were detected in the andesites. These rocks, which are composed of quartz andesite, contain high levels of K-calcalkaline. In order to determine the origins of the rocks used in the construction of the rampart walls, andesite samples were compared with other samples taken from different locations around the castle and Ankara. It was determined that the rampart andesite samples most resemble those taken from seven old quarries on Yenidogan Hill.